O pomenih besednih pozdravov - Makarovič, Gorazd (Etnolog. Nova vrsta (Ljubljana), 2013)
The article addresses the concept, functionality, types, and meanings of verbal salutations in different societies and Slovenia.
Keywords: ethnology; etnologija; ljudski običaji; Slovenci; Slovenes; komunikacija; pozdravljanje; pozdravi; zgodovinski pregledi